Low-Sidelobe Pattern Synthesis for Sparse Conformal Arrays Based on PSO-SOCP Optimization - Li, Hailin; Jiang, Yachao; Ding, Yuan; Tan, Jing; Zhou, Jianjiang (IEEE access, 2018)
This paper addresses the constrained multi-objective optimization problem of sparse conformal arrays designing. The objective of array synthesis is to find an optimal element arrangement on a conformal surface and its associated excitation strategy, which generate the main radiation beam along a pre-selected spatial direction with maximum gain and, simultaneously, suppress sidelobe levels elsewhere. A hybrid algorithm particle swarm optimization (PSO)-second-order cone programming (SOCP), comprising of PSO and SOCP, each for a dedicated purpose, is proposed to fulfill this task in this paper. More specifically, the PSO algorithm is introduced to optimize sparse conformal array element positions, whereas the SOCP is applied to seek optimal excitation coefficients for each array layout obtained. After extensive simulation with the examples of sparse circular array and sparse conical arrays, we can find that our proposed method can synthesize better radiation patterns with regard to peak sidelobe levels, compared with those obtained through other traditional algorithms.